High‐performance liquid chromatography tandem mass spectrometry method for the determination of 2CC‐NBOMe and 25I‐NBOMe in human serum. (25th July 2013) - Poklis, Justin L.; Charles, Jezelle; Wolf, Carl E.; Poklis, Alphonse
ABSTRACT: 2CC‐NBOMe 4‐chloro‐2, 5‐dimethoxyphenethyl‐ N ‐[(2‐methoxyphenyl) methyl] ethanamine and 25I‐NBOMe 2‐(4‐iodo‐2, 5‐dimethoxyphenyl)‐ N ‐[(2‐methoxyphenyl) methyl] ethanamine are of a class of N ‐benzyl phenethylamine derivatives whose synthesis was first reported in the scientific literature in 2011. Recent reports from 'personal drug experience websites' and in the popular press indicate these drugs are the latest in a series of designer 'Bath Salt' drugs of abuse. The presented high‐performance liquid chromatography triple quadrupole mass spectrometry (HPLC/MS/MS) method was developed for the detection and quantification of 2CC‐NBOMe and 25I‐NBOMe in serum of intoxicated emergency department patients. The assay applies 2‐​(2, ​5‐​dimethoxyphenyl)‐​ N ‐​(2‐​methoxybenzyl) ethanamine (25H‐NBOMe) as the internal standard. Samples were extracted using solid‐phase extraction columns. The chromatographic separation was performed on a Luna 3 µ C8 (2) 100 Å, 100 × 2.0 mm, column. Detection was accomplished by multiple‐reaction monitoring via an electrospray ionization source operating in the positive ionization mode. The calibration curves were linear over the investigated concentration range, 30–2000 pg/mL, with a lower limit of detection of 10 pg/mL for both 2CC‐NBOMe and 25I‐NBOMe. The method proved suitable for serum clinical toxicology testing. Two severely intoxicated emergency department patients were determined to have serum concentrations of 250 and 2780 pg/mL of 25I‐NBOMe using the presented method. Copyright © 2013 John Wiley & Sons, Ltd.